'Androgynous Music': Pauline Oliveros's Early Cybernetic Improvisation. Issue 4 (4th July 2021) - Gordon, Theodore
Abstract : In the late 1950s and early 1960s, Pauline Oliveros developed new techniques for improvising with new electronic instruments, which she described using language and metaphors from cybernetics and information theory. First using just a tape recorder, and later using a series of tape recorders connected to an unstable pair of oscillators, Oliveros created what she later called a 'very unstable nonlinear musicmaking system' (Oliveros, Pauline. 2016a. "Improvising Composition: How to Listen to the Time Between." In Negotiated Moments: Improvisation, Sound, and Subjectivity, edited by Gillian H. Siddall, and Ellen Waterman, 75–90. Durham, NC: Duke University Press). By positioning herself as only one member of an instrumental system that facilitated the self-regulating flow of sound as signal—operating as air pressure waves, electrical waves, psychoacoustic phenomena, and even human consciousness—Oliveros began to reconceptualize the role of her body in musical performance. By the early 1970s, Oliveros began to embrace the new kinds of musical performance and musical subjectivities produced by this system as a part of her exploration of gender in music, positing the concept of 'androgynous music'—defined as music that is simultaneously 'linear' and 'nonlinear'. Oliveros thought of her performance practice as one that could destabilise socially constructed musical identities of composition, performance, and listening, and also integrate different modalities of interacting with musical 'signal'. This article maps Oliveros's cybernetic, improvisatory practices with her earliest electronic systems, showing how her performance within these systems laid the groundwork for her later theorisations of technology, gender, and the body.